Variability in morphological and physico-chemical traits of aonla (Emblica officinalis) genotypes collected from north-eastern region of India - SINGH, A K; SINGH, P P; SINGH, SANJAY; BHARGAVA, R; MAKWANA, PURNIMA (The Indian Journal of Agricultural Sciences, 2016)
Wild aonla (Emblica officinalis Gaertn.) is found growing throughout the north eastern region of India. An extensive survey was made to identify and collect the elite genotypes at different altitude to determine variability for physical and biochemical traits and find out the promising genotypes having good fruit quality from different regions of the north-eastern region of India, i.e. Manipur, Meghalaya, Asom and Nagaland during the year of 2014-15. A total of 39 fruit samples were collected and subjected to morphological and physico-chemical characters. Wide range of variability with respect to fruit weight (1.39 - 10.59 g), fruit length (1.26- 2.53 cm), fruit breadth (1.27-2.57 cm), fruit girth (4.16 to 8.10 cm), stone weight (0.28 to 1.50 g), specific gravity (1.00-1.42), TSS of juice (10.00-21.30 oBrix), pH of fruit juice (2.48-3.41), acidity (1.80-5.84), total sugar (7.50-13.68 %), vitamin C (375.00 -1428.50 mg/100 ml of fruit juice), phenol content (944.85-4969.50 mg/100g of juice) and TSS/acid ratio (2.64-9.72) were observed among the studied genotypes. The genotype T26 was found to superior with respect to fruit weight (10.59 g), fruit girth (8.10 cm), fruit length (2.30 cm) and breadth (2.57 cm), whereas T12,. T14, T4 and T 36 were found superior with their respective qualitative characters, i.e. vitamin C, total soluble solids and total sugar among the genotypes. A wide variation in physico-chemical characters of aonla genotypes indicated that the enormous scope of selection based on their quality characters and its genetic improvement.